In Utero and Childhood Exposure to the Great Chinese Famine and Cancer in Midlife. (7th June 2021) - Zhang, Xinyuan; Wang, Gang; Forman, Michele; Fu, Qingjiang; Rogers, Connie; Wu, Shouling; Gao, Xiang
Abstract: Objectives: This study compared the risk of cancer morbidity and mortality in midlife between Chinese adults who were exposed or were not exposed to the Great Chinese Famine (1959–1961) in utero or during early childhood. Methods: The Kailuan Study Participants ( n  = 101, 125) were classified into 5 famine exposure groups by category of the year of birth: after 1961 (unexposed, reference), 1959–1961 ( in utero exposed), 1956–1958 (childhood exposed, aged 0.1–2.9 y), 1953–1955 (childhood exposed, aged 3.0–5.9 y), and before 1953 (exposed, aged 6 + y). The exposed groups were further classified by the severity of famine into less-severe or severe groups. Cancer and cancer mortality cases were confirmed by reviewing medical records from hospitals. Cox proportional hazard models were computed to examine the association between famine exposure and composite cancer events of incident cancer and cancer mortality (2006–2016), adjusting for sex, socioeconomic status, cancer-related lifestyle factors, blood C-reactive protein, and lipid profiles. Results: During a median of 10.0 years of follow-up, we identified 3, 589 incident cancer cases and 1, 940 cancer deaths. After adjustment for covariates (eg, sex, socioeconomic status, and cancer-related lifestyle factors), compared to the unexposed group, the hazard ratios (HRs) of the composite cancer events ranged 2.24–2.72 for the in utero exposed and early childhood exposed groups ( P  < 0.001 for all). When famine severity and cancer risk were examined, stratified by the famine exposure group, severe exposure to famine in early childhood, but not other birth groups was significantly associated with a higher risk of composite cancer events (adjusted HR = 1.96 for 0.1–2.9 years and HR = 1.60 for 3.0–5.9 years; P  < 0.001 for both), relative to the less-severe group. When cancer morbidity and mortality were studied separately, similar patterns were observed. Conclusions: In utero and early childhood exposures to famine, especially severe famine, were associated with a higher risk of cancer morbidity and mortality later in life. Awareness should be raised regarding the long-term effects of early life nutritional status. Funding Sources: This work was supported by the start-up grant from the College of Health and Human Development and the Department of Nutritional Sciences, the Pennsylvania State University.